2022
DOI: 10.3390/biomedicines10030629
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs in Systemic Sclerosis Patients with Pulmonary Arterial Hypertension: Markers and Effectors

Abstract: Background: Pulmonary arterial hypertension (PAH) is a major cause of death in systemic sclerosis (SSc). Early detection may improve patient outcomes. Methods: We searched for circulating miRNAs that would constitute biomarkers in SSc patients with PAH (SSc-PAH). We compared miRNA levels and laboratory parameters while evaluating miRNA levels in white blood cells (WBCs) and myofibroblasts. Results: Our study found: 1) miR-26 and miR-let-7d levels were significantly lower in SSc-PAH (n = 12) versus SSc without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In systemic sclerosis (SSc), miR-21, miR-145, miR-92a, miR4458, miR-155, and miR-202-3p upregulation is involved in pro-fibrotic pathways affecting the expression of TGFβ, metalloproteases, collagen production, and fibroblast survival. Interestingly, the circulating miRNA profile proved to be different between patients with a diffuse cutaneous form and those with a limited cutaneous one [24], and a differential miRNA expression was also found in SSc patients with pulmonary arterial hypertension (PAH) compared with those without as demonstrated in a recent study by Zaaroor Levy et al [25 ▪ ] who found lower miR-26 and miR-let-7d circulating levels in patients with PAH compared with SSc-noPAH patients. Moreover, Wuttge et al [26] showed a negative correlation between NT-pro-BNP values and miR-20a-5p or mir-203a-3p expression making them possible disease biomarkers.…”
Section: Role and Function Of Micrornas In Rheumatic Autoimmune Diseasesmentioning
confidence: 98%
“…In systemic sclerosis (SSc), miR-21, miR-145, miR-92a, miR4458, miR-155, and miR-202-3p upregulation is involved in pro-fibrotic pathways affecting the expression of TGFβ, metalloproteases, collagen production, and fibroblast survival. Interestingly, the circulating miRNA profile proved to be different between patients with a diffuse cutaneous form and those with a limited cutaneous one [24], and a differential miRNA expression was also found in SSc patients with pulmonary arterial hypertension (PAH) compared with those without as demonstrated in a recent study by Zaaroor Levy et al [25 ▪ ] who found lower miR-26 and miR-let-7d circulating levels in patients with PAH compared with SSc-noPAH patients. Moreover, Wuttge et al [26] showed a negative correlation between NT-pro-BNP values and miR-20a-5p or mir-203a-3p expression making them possible disease biomarkers.…”
Section: Role and Function Of Micrornas In Rheumatic Autoimmune Diseasesmentioning
confidence: 98%
“…Moreover, levels of TGF-β1 are decreased in SSc-PAH as compared to SSc. Increased levels of TGF-β2 and TGF-β 3 were observed in both SSc and SSc-PAH patients, but SSc-PAH had a higher level of TGF-β2 and TGF-β3 compared to SSc [119] Levy et al found that miR-26 and miR-let-7d levels were significantly decreased in SSc-PAH versus SSc without PAH and bioinformatic analysis showed that both miRNAs-regulated genes belong to TGF-β signaling pathway or Smad binding gene sets [120]. Although mutations of TGF-β receptor genes contribute to idiopathic and familial PAH, there is lack of association between TGF-β receptor gene polymorphisms and SSc-PAH.…”
Section: Tgf-β Signaling Pathwaysmentioning
confidence: 99%
“…Zaaroor Levy et al studied the circulating miRNAs that may differentiate between SSc patients with and without pulmonary arterial hypertension (PAH) and assessed their expression in plasma, white blood cells, and dermal myofibroblasts [ 5 ]. They demonstrate that plasma levels of miR-26 and miR-let-7d are decreased in SSc-PAH patients compared to SSc patients without PAH.…”
mentioning
confidence: 99%